Genetic studies on components of the Wnt signalling pathway and the severity of joint destruction in rheumatoid arthritis. Issue 5 (5th October 2012) - de Rooy, Diederik P C; Yeremenko, Nataliya G; Wilson, Anthony Gerard; Knevel, Rachel; Lindqvist, Elisabet; Saxne, Tore; Krabben, Annemarie; Leijsma, Martha K; Daha, Nina A; Tsonaka, S; Zhernakova, A; Houwing-Duistermaat, J J; et al.
Abstract : Background: Progression of joint destruction in rheumatoid arthritis (RA) is partly heritable; knowledge of genetic factors may increase our understanding of the mechanisms underlying joint destruction. The activity of the Wnt/β-catenin pathway influences osteoblast differentiation. Dickkopf-1 (Dkk-1) and sclerostin (Sost) are negative regulators and lipoprotein receptor-related protein-5 (LRP-5) and Kremen-1 are transmembrane receptors involved in this pathway. Objective: To study variants in the genes encoding these proteins in relation to progression of joint destruction. Methods: 1418 patients with RA of four cohorts with 4885 sets of hands and feet x-rays were studied. Explorative analyses were performed on 600 patients with RA from Leiden on single nucleotide polymorphisms (SNPs) tagging Dkk-1, Sost, Kremen-1 and LRP-5 . SNPs significantly associating with joint damage progression were subsequently genotyped in cohorts from Groningen (NL), Sheffield (UK) and Lund (Sweden). Data were summarised in meta-analyses. Serum levels of functional Dkk-1 and sclerostin were measured and studied in relation to genotypes. Results: In the first cohort, six Dkk-1, three Sost, one Kremen-1 and 10 LRP-5 SNPs were significantly associated with radiological progression of joint destruction. Three Dkk-1 SNPs were associated significantly with progression of joint damage in the meta-analysis, also after correction for multiple testing (rs1896368, rs1896367 and rs1528873). Two Sost SNPs tended to significance (rs4792909 and rs6503475, p=0.07 after false discovery rate correction). Gene–gene interactions between SNPs on Dkk-1 and Sost were seen. Serum levels of Dkk-1 were significantly correlated with the genotypes in rs1896368 (p=0.02). Conclusions: Patients with RA carrying risk alleles of genetic variants in Dkk-1 have higher serum levels of functional Dkk-1 and more progressive joint destruction over time.